Animal-Assisted Interventions in Pediatric and Geriatric Care: A Review of Benefits, Mechanisms, and Limitations - Magiera, Michał; Czwałga, Piotr; Sikora, Miłosz; Koprowska, Patrycja (Quality in Sport, 2026)
Background. The role of animals in modern medicine extends beyond experimental models to include the therapeutic potential of the human-animal relationship. Animal-Assisted Interventions (AAI), including Therapy (AAT), Education (AAE), and Activities (AAA), constitute an effective tool for improving patients' psychophysical well-being. These methods, utilizing appropriately trained animals (most commonly dogs) or their robotic counterparts, are applied in supporting cognitive and social functions as well as motivating activity. Aim. The aim of this review was to present the benefits of AAI in both children and adolescents, as well as in elderly patients with age-related physical, mental, and neurological disorders. Material and methods. This paper constitutes a review of recent literature, based on an analysis of data retrieved from PubMed, Google Scholar, and Web of Science databases. Only English-language publications were analyzed. Results. Analysis of studies confirms the multidimensional impact of AAI on health. In the physical sphere, contact with an animal enforces movement and sensory stimulation, improving balance and cardiovascular parameters. Regarding the psychological aspect, AAI regulates hormonal balance (oxytocin/cortisol), reducing symptoms of depression and anxiety in seniors, as well as pain and hospitalization stress in children. Although robotics offer an allergen-free alternative, interaction with a living animal, yields more lasting social effects. However, the use of AAT carries epidemiological risks and challenges regarding animal welfare, requiring strict safety procedures. Conclusions. AAI constitutes an effective, non-pharmacological support method in geriatrics and pediatrics, characterized by a unique, multidimensional nature. While the development of robotics (Pet-Robot Intervention, PRI) opens new perspectives, the success of interventions with living animals requires absolute adherence to strict safety and ethical standards.